2023
DOI: 10.3390/ijerph20032744
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Evidence Regarding Decision-Making on Contraceptive Use among Adolescents in Sub-Saharan Africa: A Scoping Review

Abstract: This scoping review mapped and synthesised existing evidence on the influence of individual, parental, peer, and societal-related factors on adolescents’ decisions to use contraception in sub-Saharan Africa (SSA). Peer-reviewed and review articles published before May 2022, targeting adolescents aged 10–19 years were searched in PubMed, MEDLINE with Full Text via EBSCOhost, PsychINFO via EBSCOhost, CINAHL with Full Text via EBSCOhost, Google Scholar, Science Direct, and Scopus databases. Seven studies were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Although a few studies (24,30) have also reported a non-significant effect of media exposure. There is evidence in literature on how effective mass media can promote accurate information about contraceptives, stimulating attitudinal and behavioural changes, increasing community awareness and mobilization and combating the spread of misinformation and socio cultural and religion myths regarding the use of contraceptives (38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies (24,30) have also reported a non-significant effect of media exposure. There is evidence in literature on how effective mass media can promote accurate information about contraceptives, stimulating attitudinal and behavioural changes, increasing community awareness and mobilization and combating the spread of misinformation and socio cultural and religion myths regarding the use of contraceptives (38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors at the individual, interpersonal, and societal levels have been identified to be related to contraceptive use, non-use (or ineffective use) among adolescents and youth [ 6 ]. Among the societal factors, the influence of religious norms is important to highlight since these norms often support high fertility (and non-use of contraception) while at the same time they condemn sexual relations outside of marriage [ 7 – 10 ].…”
Section: Introductionmentioning
confidence: 99%